The Interaction of Political, Fiscal and Financial Stability: Lessons from the Crisis - Ernest Gnan; Ewald Nowotny; András Simor; Iain Begg; Andrew Bosomworth; Ugo Panizza; Elga Bartsch; Moritz Kraemer (SUERF - The European Money and Finance Forum, 2013)
The current financial, economic and fiscal crisis is among other things characterised by complex interrelations between financial, fiscal, macroeconomic and political instability. One instability breeds another, with feedback loops generating self-reinforcing adverse cycles: The financial crisis triggered the `Great Recession'. Countermeasures by governments – to save banks and bolster up aggregate demand – ultimately jeopardized fiscal sustainability and bred the fiscal crisis. The latter in turn destabilised sovereign bond markets and banking systems in several countries. Political instability resulted from the substantial fiscal consolidations forced upon governments in the light of threatening or actual loss of access to financial market financing, and the accompanying deep recessions and sharp increase in unemployment. Political instability in turn further erodes economic and financial market confidence, thus worsening short and long-term economic and fiscal prospects, and further aggravating financial instability. In the EU and more specifically the Euro Area, multiple channels of spillovers and contagion turn the problems from purely national phenomena to ones of EU-wide and ultimately even global scope. Thus, apart from national political processes, Euro Area and EU-wide economic governance has been criticized for not addressing reform needs decisively, thus prolonging and deepening the cycle of instability.
Keywords: E5; E58; E62; E63; F34; G15; G2; 330; Financial stability; sovereign bonds; political stability; Euro Area; contagion; spillovers; crisis management; monetary policy; liquidity; fiscal consolidation; supervision; governance; banking union; sovereign ratings; Finanzkrise; Schuldenmanagement; Öffentliche Schulden